2019
DOI: 10.1108/bij-05-2018-0131
|View full text |Cite
|
Sign up to set email alerts
|

Cause-related marketing: an exploration of new avenues through conjoint analysis

Abstract: Purpose Cause-related marketing (CrM) is one of the effective marketing concepts which draw high public exposure and make the cause and the organization known in the market. Further, it develops a higher inclination of the customers associating themselves with CrM-related campaigns. In this regard, CrM campaigns generally take hedonic products into consideration. The purpose of this paper (comprises two studies) is to: study 1, examine the attributes leading to successful CrM campaign and afterward when the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 217 publications
(240 reference statements)
2
19
1
2
Order By: Relevance
“…One of the modern studies in this field confirmed the relevance of “hedo-utilitarian” products, that are useful and can bring pleasure simultaneously. They are more effective in attracting consumers, as they have cognitive and affective responses altogether (Kulshreshtha et al , 2019).…”
Section: The Role Of Procrastination In Economic Behaviormentioning
confidence: 99%
“…One of the modern studies in this field confirmed the relevance of “hedo-utilitarian” products, that are useful and can bring pleasure simultaneously. They are more effective in attracting consumers, as they have cognitive and affective responses altogether (Kulshreshtha et al , 2019).…”
Section: The Role Of Procrastination In Economic Behaviormentioning
confidence: 99%
“…CRM in general has received growing attention from marketing scholars (Galan Ladero, Galera Casquet, & Singh, 2015; Kulshreshtha, Bajpai, Tripathi, & Sharma, 2019; Lee Thomas, Mullen, & Fraedrich, 2011; Ratnakaran & Edward, 2019). As discussed previously, CRM is a common form of corporate social responsibility (CSR) activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In general, consumers are more willing to buy products from companies involved in CRM activities (Smith & Alcorn, 1991) and it is an effective way to promote both utilitarian and hedonic products (Chang, 2008; Strahilevitz, 1999). Moreover, Kulshreshtha et al (2019) conducted an innovative conjoint analysis on the effectiveness of CRM for utilitarian products having hedonic features. They defined the product type as hedo‐utilitarian products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…CrM may have a potential to progress an organization"s position in the social order and describe it like a societal responsible body. Literature also found that a realistic cause is necessary to success the CrM strategies in other words lacking with a proper and relevant "strategic fit", efforts and time invested in CrM might be ineffective [11].…”
Section: Cause Related Marketing (Crm)mentioning
confidence: 99%